2018
DOI: 10.4291/wjgp.v9.i1.28
|View full text |Cite
|
Sign up to set email alerts
|

Liver cirrhosis-effect on QT interval and cardiac autonomic nervous system activity

Abstract: AIMTo examine the impact of liver cirrhosis on QT interval and cardiac autonomic neuropathy (CAN).METHODSA total of 51 patients with cirrhosis and 51 controls were examined. Standard 12-lead electrocardiogram recordings were obtained and QT as well as corrected QT interval (QTc) and their dispersions (dQT, dQTc) were measured and calculated using a computer-based program. The diagnosis of CAN was based upon the battery of the tests proposed by Ewing and Clarke and the consensus statements of the American Diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…were prolonged in patients with cirrhosis in comparison with healthy controls and that cirrhosis patients were diagnosed more often with cardiac autonomic dysfunction. Besides that, authors found that ANS activity cardiac is affected strongly by the severity of cirrhosis and probably contributes to the development of cirrhotic myocardiopathy [34].…”
Section: Effects Of Cirrhosis On Hrvmentioning
confidence: 97%
“…were prolonged in patients with cirrhosis in comparison with healthy controls and that cirrhosis patients were diagnosed more often with cardiac autonomic dysfunction. Besides that, authors found that ANS activity cardiac is affected strongly by the severity of cirrhosis and probably contributes to the development of cirrhotic myocardiopathy [34].…”
Section: Effects Of Cirrhosis On Hrvmentioning
confidence: 97%
“…Studies suggest that increased levels of norepinephrine correlate with QTc values [29]. Furthermore, the mechanism is opposite to that in normal subjects, where excess norepinephrine produces a lower QTc [33]; a clinical consequence of the autonomic dysfunction was the lack of increased heart rate despite high levels of norepinephrine, possibly due to down-regulation of beta-receptors.…”
Section: Discussionmentioning
confidence: 97%
“…This is a linear regression-based method for cirrhosis in our association of bilirubin with QT interval. We agree that liver cirrhosis has been associated with a prolonged QT interval (Tsiompanidis et al, 2018). Nevertheless, we adjusted our models for alanine aminotransferase and aspartate aminotransferase which can be elevated in liver disease especially in nonalcoholic fatty liver disease (Sehatpour et al, 2020), a common cause of liver cirrhosis in the United States (Negro, 2020).…”
Section: Response To the Letter To The Editormentioning
confidence: 88%